2017
DOI: 10.1016/j.ijsu.2017.10.076
|View full text |Cite
|
Sign up to set email alerts
|

Mid to long term outcomes of Laparoscopic Sleeve Gastrectomy in Indian population: 3–7 year results – A retrospective cohort study

Abstract: LSG has durable weight loss at 5 year with %EWL of 61% and significant resolution of obesity associated co-morbidities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 33 publications
2
8
0
Order By: Relevance
“…In Kraljevic et al, 52.0%, and in Hauters et al, 80.0% of the LSG cohort with baseline GERD experienced ongoing or worsened reflux at follow-up; of patients without preoperative reflux, 32.4% and 43.0%, respectively, developed de novo GERD in follow-up [ 18 , 20 ]. While there are centers that have reported favorable mid-term LSG outcomes with respect to GERD [ 29 , 30 ], the implications for complications due to both pre-existing and de novo GERD remain among the most important considerations for selection of this procedure. In the present study, about half of the patients reported that they suffered from heartburn or took any drugs to treat heartburn.…”
Section: Discussionmentioning
confidence: 99%
“…In Kraljevic et al, 52.0%, and in Hauters et al, 80.0% of the LSG cohort with baseline GERD experienced ongoing or worsened reflux at follow-up; of patients without preoperative reflux, 32.4% and 43.0%, respectively, developed de novo GERD in follow-up [ 18 , 20 ]. While there are centers that have reported favorable mid-term LSG outcomes with respect to GERD [ 29 , 30 ], the implications for complications due to both pre-existing and de novo GERD remain among the most important considerations for selection of this procedure. In the present study, about half of the patients reported that they suffered from heartburn or took any drugs to treat heartburn.…”
Section: Discussionmentioning
confidence: 99%
“…Ultimately, 49 original articles were included, as shown in the study flowchart( Table 1 ). [ [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] , [59] , [60] , [61] , [62] , [63] , [64] , [65] , [66] , [67] , [68] , [69] ].…”
Section: Resultsmentioning
confidence: 99%
“… 36 Genco et al [ 45 ] Gastroesophageal reflux disease and Barrett's esophagus after laparoscopic sleeve gastrectomy: a possible, underestimated long-term complication 2017 162 45.8 ± 6.3 visual analogue scale (VAS) evaluation of GERD symptoms, PPIs consumption recording, esophagogastroduodenoscopy (EGD) 58 33.6 68.1 48 Georgia et al [ 46 ] 24-h multichannel intraluminal impedance PH-metry 1 year after laparoscopic sleeve gastrectomy: an objective assessment of gastroesophageal reflux disease 2017 12 48.97 24-h multichannel intraluminal impedance-pH metry (MIIpH) pre-and 12 months post-LSG; symptoms; EGD 12 42.06.00 83.33 38 Hendricks et al [ 47 ] Impact of sleeve gastrectomy on gastroesophageal reflux disease in a morbidly obese population undergoing bariatric surgery 2016 919 N.R. symptoms, PPI treatment, upper gastrointestinal endoscopy (UGI), esophagogastroduodenoscopy (EGD), pH manometry 24 group B 1% (13) group A 3% (25) 38 Himpens et al [ 48 ] Long-term results of laparoscopic sleeve gastrectomy for obesity 2010 53 39 (range, 31–57; SD, 5.4) Bariatric analysis and reporting outcome system (BAROS) score 72 3.3 23 34 Hirth et al [ 49 ] Laparoscopic sleeve gastrectomy: long-term weight loss outcomes 2015 16 43.5 medi...…”
Section: Resultsmentioning
confidence: 99%
“…24 In a relatively large study including 424 obese patients in India, complete improvement in obstructive sleep apnea, 69.3% improvement in hypertension, 75% improvement in hypothyroidism was shown after LSG. 25 Kikkas and colleagues in a recent investigation have shown that LSG ensured long-term excess weight loss 61.0% at 5 years. They concluded that LSG has a long-term effect on the significant improvement of triglycerides, low-density lipoproteins, and high-density lipoproteins, but not on total cholesterol levels.…”
Section: Discussionmentioning
confidence: 96%